Development of Oil Palm Empty Fruit Bunch Cement Boards Based on Forming Technique - Vathivellu, Balayokee; Nik Mohd Zaini Nik Soh (Recent Trends in Civil Engineering and Built Environment, 2026)
The utilization of OPEFB, an abundant agricultural waste from the palm oil industry, as a raw material in cement boards contributes to sustainable waste management practices and reduces reliance on traditional wood-based materials. This research project focuses on the development of oil palm empty fruit bunch (OPEFB) cement boards using 2 method which is manual forming and vibration forming but three different techniques which is two-layer forming method, hand-manual forming with a three-layer but one compaction method as a controlled method and also the vibration technique. The study begins by collecting OPEFB fibers from local palm oil mills and processing them to obtain suitable fiber density, 1300kg/m3, dimensions which is 350mm x 350mm x12mm and moisture content with 40%. The fibers are then mixed with cement and water to form a composition mixture. Three techniques are employed to shape the cement boards. In the controlled method which is the hand-manual forming with three layers but one compaction method, the fibre is evenly distributed three times into the mould using sieve and it is compacted once to form the shape, whereas the two-layer forming method is where the fibre is divided into 2 and then it is evenly distributed and first compaction is done and then the remaining fabricated mould will be even distributed again and the second compaction will be done. Conversely, the vibration technique involves using a vibrating table to ensure even distribution of the composition mixture within the molds, resulting in more consistent board properties. The produced cement boards are subjected to a comprehensive set of tests to evaluate their physical and mechanical properties, including density, thickness swelling, Modulus of Rupture, Modulus of Elasticity and also internal bonding. Comparative analyses are conducted to assess the differences in performance between the hand-formed and vibration-formed boards. At the end of this research, it is proved that the two-layer forming method has given the best results in both mechanical and physical properties.